Characteristics of enrichment of fresh pasta with bee drone broods flour - Correia, Paula (2024)
Background: The fortification of staple food is one of the goals of modern technologies. Aim: In this study, preparation of pasta replacing wheat semolina flour with drone brood flours, rich in protein (27-38%), was tested. Method: The drone brood flour (DF) was obtained by the cold (CE) and hot (HE) extraction processes. After several trials, it was possible to incorporate 10% DFCE, and 20% DFHE. Pastas were evaluated in terms of its technological characteristics (optimum cooking time, cooking losses, swelling index), physical characteristics (colour and texture), chemical characteristics (nutritional composition) and sensory characteristics, and compared with a control pasta (0% dwarf flour). Results and discussion: The addition of DF increased the optimum cooking time, cooking loss and swelling index. The water absorption increased in the case of 10% DFCE pasta. The incorporation of DFCE caused a darker final product, however the incorporation of DFCE resulted in a slightly lighter product when compared to the control sample. In general, the addition of DF led to an increase in the hardness of pastas, particularly in the 20% DFHE samples. Moreover, pasta with added DF had a higher protein and ash content, thus increasing its nutritional quality. Sensorially, the DF pastas had an overall appreciation and a preferential purchase intention by the tasters, standing out in terms of the intensity of colour and aroma compared to the control pasta. Conclusion: DF is a promising ingredient in pasta production, contributing to human health and at the same time promoting economic returns.